MODELING THE DRYING CHAMBER AND OPTIMIZATION OF INPUT PARAMETERS USING THE SOLIDWORKS DESIGN STUDY TOOL - KROSHNYY, IGOR; RUBINSKYY, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article describes the optimization of the drying chamber input parameters and its operation mode using SolidWorks Simulation software. One of the main tasks in the design of drying chambers is to ensure uniform temperature distribution in the stack to achieve efficient drying of materials. In this regard, this study determines the optimal parameters of the chamber design and its operating mode to ensure stable drying conditions. The methodology includes the creation of a 3D model of the drying chamber and its main components in SolidWorks, the construction of a numerical mesh, thermal analyses in SolidWorks Simulation, and the use of the Design Study module to optimize design parameters and operating conditions. The results of the research include an analysis of the distribution of heat flows in the stack, as well as temperature measurements at various points in the model. This allows us to estimate temperature gradients and their dependence on optimization parameters. The temperature measurements were performed using the Prob tool, which takes into account the geometric features and the exact location of the nodes on the tetrahedral elements of the numerical grid. The study is based on an integrated approach to designing drying chambers using SolidWorks and automating the optimization process through the SolidWorks API. For this purpose, specialized software was created that allows users to enter input data for modeling, transfer thermal analysis parameters to SolidWorks, and perform calculations in the background. The functionality of the developed software includes automated display of results in a special program window, which significantly reduces the time for obtaining data. Reducing the calculation time is also achieved by eliminating the visualization of intermediate processes, which is important for further improvement of drying processes for various materials.
Keywords: Software; SolidWorks Simulation; Thermal study; Wood drying; Computer-aided design